2009
DOI: 10.1038/onc.2009.370
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of peroxisome proliferator-activated receptor-β induces less differentiation and enhances cell–fibronectin adhesion of colon cancer cells

Abstract: The role of peroxisome proliferator-activated receptor-b/ d (PPAR-b/d) in the pathogenesis of colon cancer remains highly controversial. This study specifically silenced the PPAR-b expression in three colon cancer cell lines with different metastatic potentials. Although PPAR-b knockdown resulted in more malignant morphological changes, bigger colony sizes and lower carcinoembryonic antigen (CEA) secretion, and enhanced the cell-fibronectin adhesion, cell invasion and migration were unaffected. These effects w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
28
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 44 publications
8
28
0
Order By: Relevance
“…However, the mechanisms underlying this elevated ILK expression remained unclear. Previous studies showed that ILK expression can be upregulated by hypoxia (Abboud et al, 2007), inhibition of ubiquitin-mediated degradation through binding to PINCH (Legate et al, 2006) or peroxisome proliferator-activated receptor-mediated transcriptional repression (Yang et al, 2010). These data suggest that the cause of ILK upregulation may vary depending on tumor type.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…However, the mechanisms underlying this elevated ILK expression remained unclear. Previous studies showed that ILK expression can be upregulated by hypoxia (Abboud et al, 2007), inhibition of ubiquitin-mediated degradation through binding to PINCH (Legate et al, 2006) or peroxisome proliferator-activated receptor-mediated transcriptional repression (Yang et al, 2010). These data suggest that the cause of ILK upregulation may vary depending on tumor type.…”
Section: Discussionmentioning
confidence: 74%
“…ILK overexpression and deregulation are frequently observed in a wide variety of human cancers, further implicating ILK in tumorigenesis and cancer progression (Yoganathan et al, 2000;McDonald et al, 2008). Although it is known that ILK protein is stabilized through binding to PINCH (particularly interesting Cys-His-rich protein) (Legate et al, 2006) and that ILK transcription is regulated by peroxisome proliferator-activated receptor (Di-Poi et al, 2002;Yang et al, 2010), the mechanisms of ILK upregulation in cancer cells are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments that examined polyp formation in PPAR d-null APC min mice show either no effect (18), or paradoxically, an increase in polyp number and size compared with wildtype mice (13,16,17,19). Our recent study shows that PPAR d may facilitate the differentiation of colon cancer cells (20). Collectively, the role of PPAR d in colorectal carcinogenesis remains highly controversial.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of PPAR d had been stably silenced in the cells treated by Lenti-PPAR d while remaining unaffected in the Lenticontrol treated cells, as confirmed in our previous study (ref. 20; see Supplementary Data). Of the 3 cell lines, KM12C has poor metastatic potential, whereas KM12SM and KM12L4a have high metastatic potentials (28).…”
Section: Cell Culturementioning
confidence: 99%
See 1 more Smart Citation